2021
DOI: 10.1016/j.paid.2020.110504
|View full text |Cite
|
Sign up to set email alerts
|

Is the COVID-19 pandemic even darker for some? Examining dark personality and affective, cognitive, and behavioral responses to the COVID-19 pandemic

Abstract: As the COVID-19 pandemic and interventions intended to minimize its spread continue to impact daily life, personality research may help to address the different ways in which people respond to a major global health crisis. The present study assessed the role of dark personality traits in predicting different responses to the pandemic. A nationally representative sample of 412 Americans completed measures of the Dark Tetrad as well as perceptions of COVID-19 threat, emergency beliefs, and positive and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 30 publications
5
61
1
3
Order By: Relevance
“…In Bangladesh, despite that fear, respondents were mostly positive, indicating that they believed the disease was “controllable and containable” ( Hossain et al., 2020 ). In a small sample of Americans, depending on the “dark” personality trait (narcissism, Machiavellianism, psychopathy, and sadism), COVID-19 was perceived either as a threat of instability or as a positive protective measure ( Hardin et al., 2020 ). In the Balkans (Bosnia and Herzegovina), fear was associated with older individuals, and depression with younger ones ( Šljivo et al., 2020 ).…”
Section: Coronex: Possible Primary and Secondary Influencing Or Inducmentioning
confidence: 99%
“…In Bangladesh, despite that fear, respondents were mostly positive, indicating that they believed the disease was “controllable and containable” ( Hossain et al., 2020 ). In a small sample of Americans, depending on the “dark” personality trait (narcissism, Machiavellianism, psychopathy, and sadism), COVID-19 was perceived either as a threat of instability or as a positive protective measure ( Hardin et al., 2020 ). In the Balkans (Bosnia and Herzegovina), fear was associated with older individuals, and depression with younger ones ( Šljivo et al., 2020 ).…”
Section: Coronex: Possible Primary and Secondary Influencing Or Inducmentioning
confidence: 99%
“…Finally, future longitudinal studies on perceived stressfulness of the COVID-19 pandemic could focus on additional individual difference characteristics as predictors. For instance, recent cross-sectional studies have examined personality dimensions based on reinforcement sensitivity theory (e.g., reward reactivity; Bacon & Corr, 2020), as well STRESSFULNESS OF COVID-19 22 as "dark personality traits" (e.g., narcissism, sadism; Hardin et al, 2020) in this context.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…In a different study, Wagerman et al [ 21 ] investigated and revealed that anxious attachment positively determined the COVID-19 distress factor. Hardin et al [ 22 ] analyzed and discovered that Machiavellianism and Narcissism introduced negative impacts in response to COVID-19 in the U.S. context.…”
Section: Introductionmentioning
confidence: 99%